EFEKTIVITAS PERJANJIAN PERKAWINAN PRA NIKAH DALAM MELINDUNGI SUAMI ISTRI DAN PANDANGAN HUKUM ISLAM TERHADAPNYA - Muhammad Hilmi Ajjahidi (SAMAWA, 2023)
Marriage is a form of the union of two human beings united by a strong bond, the purpose of uniting the two male and female humans in the form of a household is to realize a sakinah family, mawaddah wa rahmah or a peaceful and loving family. One way to achieve the purpose of marriage is to make a marriage agreement between the two parties before entering into a marriage contract. In this study, it uses normative-empirical juridical research by basically combining a normative legal approach with the addition of various empirical elements using the method of approach to the law approach method. This type of research is library research which is descriptive analytical. And the results of this study explain the law of the ability of marriage agreements in Islam but must be in accordance with the provisions of the Islamic shari'a, and in the Marriage Agreement Law it is regulated in several regulations including those listed in Presidential Instruction No. 1 of 2974 and article 47 of the Compilation of Islamic Law and also contained in the Civil Code part 1 Article 139-147 and so on